Patient profiles and their relationship with the CES-D scale at the Diabetes Center for Puerto Rico - Rodríguez, José R.; Rodríguez, Rosa Janet; Disdier, Orville M. (Puerto Rico Health Sciences Journal, 2007)
Purpose: The prevalence of diabetes mellitus in Puerto Ricans has been identified and reported as being disproportionately higher as compared to other metabolic pathologies. Recently, diabetes has been identified as the third cause of mortality in Puerto Rico (Puerto Rico Health Department, Vital Statistics Annual Report, 1999-2001). The Research Center, Education and Medical Services for Diabetes in Puerto Rico (also known as the “Centro de Diabetes para Puerto Rico” [CDPR]) is a public corporation in the island created by the government to reduce diabetes prevalence, mortality and morbidity. Method: The CDPR offers Diabetes Self Management Educational Training Program Schools for patients (DSMETPS) island wide. The research design was an ex-post facto. As part of the process, patients are administered an extensive sociodemographic and health information questionnaire, which also includes the CES-D (a symptomatology depressive scale). This study pretends to describe the diabetic patient profiles (n=27) using information from the DSMETPS of the CDPR and explore the association with the CES-D. Variables such as patients’ needs, knowledge and understanding of the condition (i.e., pathology management, type and medications utilized and exercise and nutritional patterns), patient attitudes to diabetes and their relations with the CES-D were explored. Results: Results show a negative association, controlling for age and gender, between patients diabetic education/knowledge and CES-D score. Conclusions: Diabetes educators in Puerto Rico need to identify depressive symptomatology in order to prevent mental health complications in their patients since this may affect their future treatment and prognosis. An interdisciplinary team is recommended to improve the effectivity of the intervention.